RECOGNITION OF EARLY CHILDHOOD EDUCATION THROUGH INDEPENDENT LEARNING - Sri Haryanto; Robingun Suyud El Syam (Jurnal Scientia, 2023)
This article aims to explore how recognition of early childhood education through the Independent Learning Curriculum, especially how the term play with learning can be maximized through the entrance to the Free Learning Curriculum. Research is a qualitative type with the library research method, aimed at describing an object, phenomenon in narrative writing. The data collection process utilizes library research through various sources such as laws, books, journals, newspapers, web, magazines or documents, then analyzed by content analysis. Early age is a golden period for human development, where this period is the foundation for further education. In early childhood learning must be packaged in the form of a game that is appropriate for the child's age, therefore learning situations, procurement and organization of learning facilities must be designed for learning activities while playing. The concept of Independent Learning is in line with the concept of early childhood education, namely giving freedom to children to choose the learning activities they want and fulfilling children's rights to play. This is a great opportunity for early childhood education institutions to explore learning activities that are connected to various disciplines. The implications of learning innovation research through various disciplines require further research. This study focuses on the recognition of early childhood education in the Independent Learning curriculum. This shows a great opportunity in the new curriculum, where previous research did not find this aspect.